Hepcidin and erythroferrone response to 3 weeks of exposure to normobaric hypoxia at rest in trained cyclists - Płoszczyca, Kamila; Czuba, Miłosz; Chalimoniuk, Małgorzata; Witek, Konrad; Baranowski, Marcin (Frontiers in Physiology, 2023)
Purpose: The effectiveness of altitude training on haematological adaptations is largely dependent on iron metabolism. Hepcidin and erythroferrone (ERFE) are key iron-regulating hormones, yet their response to altitude training is poorly understood. The aim of this study was to analyze changes in hepcidin and ERFE under the influence of 3 weeks of the Live High-Train Low (LH-TL) method. Methods: Twenty male trained cyclists completed a 3-week training program under normoxic conditions (NORM) or with passive exposure to normobaric hypoxia (LH-TL; FiO2 = 16.5%, ∼2000 m; 11–12 h/day). Hepcidin, ERFE, hypoxia inducible factor-2 (HIF-2), ferroportin (Fpn), erythropoietin (EPO), serum iron (Fe) and hematological variables were assessed at baseline (S1), then immediately after (S2) and 3 days after (S3) intervention. Results: In the LH-TL group, hepcidin decreased by 13.0% (p < 0.001) in S2 and remained at a reduced level in S3. ERFE decreased by 28.7% (p < 0.05) in S2 and returned to baseline in S3. HIF-2α decreased gradually, being lower by 25.3% (p < 0.05) in S3. Fpn decreased between S1 and S2 by 18.9% (p < 0.01) and remained lower during S3 (p < 0.01). In the NORM group, in turn, hepcidin levels increased gradually, being higher by 73.9% (p < 0.05) in S3 compared to S1. No statistically significant differences in EPO were observed in both groups. Conclusion: Three weeks of LH-TL suppresses resting hepcidin and ERFE levels in endurance athletes. We found no association between hepcidin and ERFE after LH-TL. Probably, ERFE is not the only factor that suppresses hepcidin expression in response to moderate hypoxia, especially in later stages of hepcidin downregulation. With the cessation of hypoxia, favorable conditions for increasing the availability of iron cease.